Unregistered Marriage and the Legal Impact, A Book Review “Kepastian Hukum Perkawinan Siri dan Permasalahannya” Zainuddin SH MH & Afwan Zanuddin SH MH, Deepublish Yogyajarta, 95 Pages, ISBN: 978-602-435-120-1 - Gufron, Dede Muhammad (Indonesian Journal of Advocacy and Legal Services, 2021)
This book explains the legal certainty aspects of unregistered marriages in Indonesia. Unregistered marriages have many implications, especially with regard to law, child status, and inheritance. The book "Kepastian HukumPerkawinan Siri & Permasalahannya", explaina how is the connection between the Islamic law and the State law in marriage cases and how unregistered marriage is most certainly a bad thing. The book also explains what effects and consequences that caused by the unregistered marriage according to law.